(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Introduction: Higher education serves as a hub for diverse intellectual endeavors, where every student aims to demonstrate the distinctive qualities of an educated individual. Aim of the study: The primary objective of this research is to assess the efficacy of using activity-based learning strategies in ESL classrooms: A Case Study in Selected Districts of Karnataka Material and method: This study used a quasi-experimental research strategy to conduct quantitative research. Conclusion: The findings have been derived from the outcomes of hypothesis testing and subsequent debate. The use Using an activity-based learning (ABL) strategy significantly affects how much control students have over their own education.